360-degree cervical spinal arthrodesis for treatment of pediatric cervical spinal tuberculosis with kyphosis. Issue 1 (December 2016) - Zeng, Hao; Shen, Xiongjie; Luo, Chengke; Xu, Zhengquan; Zhang, Yupeng; Liu, Zheng; Wang, Xiyang; Cao, Yong
Abstract Background There is limited evidence to guide treatment for pediatric cervical spinal tuberculosis with kyphosis (PCSTK). This study retrospectively evaluates the safety, feasibility and efficacy of 360-degree arthrodesis combined with anterior debridement and decompression for treating PCSTK, while simultaneously emphasizing the role of posterior fixation for the correction and maintenance of the kyphosis angle. Methods From May 2006 to December 2012, a total of 12 children with PCSTK underwent 360-degree cervical spinal arthrodesis followed by debridement of focus and decompression of the spinal cord. Data on the angle of kyphosis correction, visual analogue scale scores of pain, the American Spinal Injury Association scoring system of nerve function scores, erythrocyte sedimentation rate (ESR) and body weight were collected at certain periods. Clinical efficacy was evaluated by statistical analysis based on collected data. Results Average follow-up period was 34.3 ± 8.6 months. No postoperative complications related to the instrumentation occurred, and neurologic function improved in various degrees. Preoperative kyphosis angle was 41.4 ± 5.2°, and significantly decreased to -4.9 ± 4.9° after surgery. The correction of kyphosis and loss of correction were 47.1 ± 4.9° and 0.6 ± 1.4°, respectively. Average pretreatment ESR was 49.8 ± 13.2 mm/h, which normalized (8.5 ± 0.6 mm/h) within three months in all patients. Average preoperative visual analogue scale was 6.6 ± 1.6, which decreased to 2.3 ± 1.4 postoperatively and 0.3 ± 0.5 during the final follow-up. Mean preoperative body weight was 25.9 ± 5.1 kg, and body weight was 33.5 ± 4.8 kg at the third month of post-operation. Bone healing was achieved in all patients after a mean period of 5.4 months. Conclusions 360-degree arthrodesis combined with anterior debridement and decompression is a safe and effective method for the treatment of PCSTK. For the correction and maintenance of the kyphosis angle, additional posterior fixation is recommended.